Pop-up Polanyi: Cultural entrepreneurs and the 'vacancy fix'. (September 2018) - Scott, Michael; Szili, Gerti
Abstract: Gentrification as an urban strategy pivots upon the dual mediation of the city as a site for aesthetic consumption and pleasure, and as a space of potential ground rent. The recent rise of urban regeneration programs that assist small scale cultural entrepreneurs into disused commercial property – 'pop-up shops' – is one example of the convergence of the urban cultural economy and gentrification. This article presents a preliminary explanation of the function of such urban programs through Karl Polanyi's socioeconomic concepts and the case of Renew Adelaide. It is argued that Renew aligns and then stabilises different Polanyian modes of economic integration (reciprocity, redistribution, and exchange), while inducing a partial and temporary de-commodification of urban space. This approach outlines how 'pop-up' programs contain multiple objectives. First, they induce the images of creative city vibrancy that can be folded into contemporary place marketing. Second, they enable celebrated entrepreneurial subjectivities to be performed. Third, they illustrate how 'vacancy fixes' are addressed via small-scale cultural projects supporting land banking for the owners of properties whose rent gaps have yet to be closed. This Polanyian approach explains how the modes of integration undergirding these programs are assembled via an orientation to the real or symbolic processes of gentrification. Highlights: Polanyian analysis of short term 'pop-up' shops. Case study of Renew Adelaide and 'low budget' urban renewal policy. Explanation of how pop up shops are a 'vacancy fix' oriented to managing the rent gap. Discusses how pop-ups span the urban cultural economy and gentrification. Illustrates how urban land and labour are temporarily and partial de-commodified.. Illustrates how low budget urban renewal policy is woven into the economies of signs and space.